SUPPORTING AND INHIBITING FACTORS OF PEDAGOGIC COMPETENCE OF ISLAMIC EDUCATION TEACHERS AT SMA SWASTA MUHAMMADIYAH 02 MEDAN - Abrianto, Danny; Tumiran, Tumiran; Rangkuti, Charles; Umat, Hardakwah (Proceeding International Seminar of Islamic Studies, 2024)
Supporting and inhibiting factors of pedagogic competence of Islamic Education teachers at SMA Swasta Muhammadiyah 02 Medan represent a crucial area of study for enhancing the quality of education within Islamic institutions. This abstract aims to summarize key findings and insights into the dynamics influencing the pedagogical capabilities of educators in this specific context. The research identifies various supporting factors that bolster the pedagogic competence of Islamic Education teachers, including continuous professional development programs, access to educational resources, supportive school administration, and a collaborative teaching environment. These elements are instrumental in fostering an atmosphere conducive to effective teaching and learning, enabling teachers to develop and refine their instructional strategies and methodologies. Conversely, the study also highlights several inhibiting factors that challenge the pedagogic competence of teachers. These include inadequate infrastructure, limited access to modern teaching aids and technology, insufficient training opportunities, and socio-cultural constraints. Additionally, bureaucratic hurdles and lack of motivation among teachers further exacerbate the challenges to pedagogic competence. The research underscores the importance of addressing these inhibiting factors while strengthening the supporting elements to enhance the pedagogic competence of Islamic Education teachers at SMA Swasta Muhammadiyah 02 Medan. It suggests that a holistic approach involving policy reforms, infrastructure development, and enhanced professional development opportunities is essential for empowering teachers and enriching the educational experience for students. By focusing on both the enablers and barriers to pedagogic competence, stakeholders can implement more effective strategies for teacher development and educational improvement in Islamic schools.